"Sexual Ornament" or "Spiritual Trainer"? Envisioning and Marketing to a Female Audience Through the NHL's "Inside the Warrior" Advertising Campaign. (June 2015) - Gee, Sarah
This study investigates the unique association between female hockey fans, dominant conceptions of gender in sport, and the role of cultural intermediaries in the cultural production of media texts. In particular, it focuses on the National Hockey League's "Inside the Warrior" advertising campaign created by marketing agency Conductor (for the relaunch of the League after the 2004–2005 lockout), that was, in part, envisioned for and marketed to target female audience. Using insights revealed through in-depth semistructured interviews with two cultural intermediaries, the critical analysis in this article focuses on how the cultural intermediaries from Conductor imagined and conceptualised female hockey fans as a target audience, engages in a comparative analysis between the creative strategies in the production of the "Inside the Warrior" campaign and characteristics of female narratives to attract a female audience, and discusses the accommodation of resistance to the stereotypical representations of gender in the "Inside the Warrior" campaign by the cultural intermediaries. These insights serve to highlight the hegemonic position of cultural intermediaries and the disjuncture between the encoding by producers and the interpretation by consumers and fans.